A perspective on New Zealand universities - Jager, Lain (New Zealand Science Review, 2010)
The trouble with change is that it always annoys the heck out of someone. As President Obama has found recently, change in the education or health systems is towards the more challenging end of the spectrum. Let me start by asserting that: the future is bright if we can grasp it; money is short and we need to do a better job of earning it; and the pathway to success is about focused excellence because as a small country we will simply never be world-class at everything. So, as with all things in life, it’s about the choices we make and our determination to succeed.